Pelatihan Membuat Sediaan Masker Gel “peel off “ Dengan Bahan Alam Daun Kelor Sebagai Kosmetik Untuk Mencegah Penuaan Dini Pada Kulit muka - Jumain Jumain; Asmawati Asmawati (Jurnal Pengabdian Kefarmasian, 2022)
Today the role of family members (mothers) in increasing income is still very small, housewives can help support family income, although now many have jobs outside the home, but many more stay at home, including young girls who drop out of school . Various skill activities that can be done by housewives and young women to increase family income, including making products made from raw materials that are cheap and easy to obtain and easy to produce. The results of the study of fresh Moringa leaves showed that the antioxidant power was 7 times stronger than Vitamin C. Rizkayanti's research, 2017 showed that the antioxidant activity of Moringa leaf extract IC50 = 22.18 bpj in the category of very strong antioxidant activity. Based on this, the community service team tried to apply it, so that Moringa can be used as a raw material for cosmetic products, namely "Feel Off" gel masks. The implementation of the activity begins with making an MOU on the kelurahan side, reviewing the area where the activity is carried out. A socialization was held on April 9, 2021 and the implementation of community service on April 10, 2021 was attended by 20 participants. Before giving the material and practice of making masks, a pre-test was conducted with the aim of seeing the participants' knowledge of the material provided, from the results of the Fre-test that 7 people (35%) participants had the knowledge and skills in the low category. After the training and practice, conducted a post test, 18 people (90%) knew the material was given and were skilled in making the "Peel Off" mask product which was categorized as good.Keywords: “Peel Off” Gel Mask, Moringa leaf extract, premature aging.Dewasa ini peranan anggota keluarga (ibu)   dalam meningkatkan penghasilan masih sangat kecil, Ibu  rumah tangga dapat membantu menopang penghasilan keluarga, walaupun sekarang  sudah banyak  memiliki pekerjaan diluar rumah, tetapi masih lebih banyak lagi tinggal di rumah saja, termasuk para remaja putri yang putus sekolah. Berbagai kegiatan keterampilan yang dapat dilakukan oleh ibu rumah tangga dan remaja putri untuk menambah penghasilan keluarga, diantaranya membuat produk berbahan baku murah dan mudah didapatkan serta mudah diproduksi. Hasil penelitian  daun kelor segar menunjukkan kekuatan antioksidan 7 x lebih kuat di banding Vitamin C. Penelitian Rizkayanti, 2017 menunjukkan aktivitas antioksidant ekstrak daun kelor IC50 = 22.18 bpj kategori aktivitas antioksidan sangat kuat. Berdasar hal tersebut, maka  tim pengabmas  mencoba mengaplikasikannya, sehingga dapat dimanfaatkan  Kelor sebagai bahan baku  produk kosmetik yaitu  Masker gel “Feel Off”. Pelaksanaan kegiatan diawali  membuat MOU pada pihak kelurahan, Meninjau daerah tempat  kegiatan. Diadakan sosialisai pada tgl 9 April  2021 dan pelaksanaan kegiatan  tgl 10 April 2021 diikuti 20 orang peserta. Sebelum  pemberian materi dan praktek pembuatan Masker, terlebih dahulu dilakukan pre-test dengan tujuan tmelihat pengetahun peserta mengenai materi yang diberikan, dari hasil Fre-test bahwa 7 orang  (35 %)  peserta mempunyai pengetahuan dan  keterampilan termasuk  kategori  rendah. Setelah dilakukan pelatihan dan  praktek, dilakukan melakukan post tes di peroleh 18 orang ( 90%)  mengetahui  materi diberikan dan terampil dalam  membuat produk Masker “Peel Off “dikategorikan baik.Kata Kunci : Masker Gel “Peel Off”,  ekstrak daun Kelor, penuaan dini.